Os reflexos da pandemia de covid-19 na atuação das Bibliotecas Universitárias e as condições de ensino: o caso dos estudantes de ações afirmativas do curso de Biblioteconomia do estado do Rio de Janeiro - (:unkn) unknown (INSTITUTO BRASILEIRO DE INFORMAÇÃO EM CIÊNCIA E TECNOLGIA / UNIVERSIDADE FEDERAL DO RIO DE JANEIRO, 2024)
The period of social isolation experienced due to the COVID-19 pandemic brought numerous challenges to the educational system with increased access to digital devices and the internet in the teaching process. Thus, new methodological adaptations were implemented, so that teaching and learning did not stop, adopting the Emergency Remote Teaching model. Within this scenario, the present thesis aims to analyze the perception of Library Science students – from UFRJ, UNIRIO, and UFF – resulting from affirmative actions on access to information and knowledge during the period of the COVID-19 pandemic, in the context of university libraries of the Federal Universities of the state of Rio de Janeiro. This is an applied research, with a qualitative and quantitative approach, with exploratory objectives. To this end, bibliographical research– as a technique for understanding the relevance of the topic to be studied – and documentary research were adopted, using diverse and dispersed primary sources, made available through official documents, newspapers, statistical tables, newspapers, magazines, reports, live experiences, etc. These helped to build the theoretical framework based on the concepts of inequality, info-exclusion, mediation, university library and social infrastructure, establishing a connection between affirmative action students and the impacts of the pandemic on the performance of university libraries and the teaching and learning process. As a data collection instrument, a questionnaire was applied to Library Science students at federal universities in the state of Rio de Janeiro. The study made it possible to observe that university libraries mobilized themselves to serve users. As for students, the results obtained through the application of the questionnaire point to the difficulties faced by them, their perception of the actions of university libraries, and the fears experienced during the pandemic. Thus, the hypothesis raised – that students who entered university through affirmative action policies encountered greater difficulties in the teaching and learning process in the face of the new scenario imposed by ERE – can be confirmed.
Keywords: Pandemia; Ensino superior; Biblioteca universitária; Desigualdade; Ações afirmativas; Ciência da Informação; Pandemic; Teaching; University library; Inequality; Affirmative action; Information Science; Ciência da informação